1997
DOI: 10.1183/09031936.97.10051041
|View full text |Cite
|
Sign up to set email alerts
|

Atopy, lung function and bronchial responsiveness in symptom-free paediatric asthma patients

Abstract: In adolescence, some paediatric asthma patients will become symptom-free and require no further treatment. There is little information on the atopic status, lung function and bronchial responsiveness of these patients.Symptom-free asthma patients (n=118) aged 7.7-19.2 yrs, were evaluated 1 year after termination of therapy. Bronchial asthma had previously been diagnosed on the basis of recurrent wheezing episodes. Atopic status was assessed by skin-prick testing. Baseline lung function was measured by spiromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
(58 reference statements)
1
14
0
1
Order By: Relevance
“…It is now clear that wheezing during preschool years is a heterogeneous condition that may be transient in many children [15]. The children who did not develop AH and remained asymptomatic after withdrawal of ICS in this study could thus be viewed as transient wheezers without AH [16,17]. The present findings of a higher prevalence of atopic sensitization in children with AH than in those without AH is in agreement with earlier findings in such transient wheezers [15].…”
Section: Discussionsupporting
confidence: 83%
“…It is now clear that wheezing during preschool years is a heterogeneous condition that may be transient in many children [15]. The children who did not develop AH and remained asymptomatic after withdrawal of ICS in this study could thus be viewed as transient wheezers without AH [16,17]. The present findings of a higher prevalence of atopic sensitization in children with AH than in those without AH is in agreement with earlier findings in such transient wheezers [15].…”
Section: Discussionsupporting
confidence: 83%
“…50 Finally, another subset of patients with severe nonallergic asthma has predominately neutrophils on sputum induction. 26,49 Despite these observations, the results of other studies support extension of the importance of allergen sensitization to patients with severe or difficult-to-treat asthma as well. 9 As anticipated, we were unable to demonstrate associations between aeroallergen sensitivity and genotype differences at the 16th position of the b-receptor gene.…”
Section: Discussionmentioning
confidence: 77%
“…Spirometric values and peak flows might not reflect the degree of inflammation in the airways; however, correlations between sputum eosinophilia and inflammation have been repetitively noted and would be expected to move in tandem with eNO and PC 20 values. 3,[43][44][45][46][47][48][49] We suspect that if we included all severities of asthma instead of the inclusion of only mild-to-moderate asthma that a correlation between skin testing and sputum eosinophils would have been positive. Nonetheless, the strong statistical correlations between eNO, PC 20 , and IgE values and positive skin test responses suggest that allergy is an important factor in inflammation in mild-to-moderate asthma and that allergen avoidance or other allergy-directed measures might reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the AAO children, there were no clinical differences between those with elevated eosinophils and those without. GRUBER et al [7] have shown that atopic asthmatic children in remission have evidence of pulmonary function abnormalities and bronchial hyperresponsiveness. However, it was not clear whether these findings were suggestive of continuing airways inflammation, or merely indicative of previous airway damage.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic airways inflammation plays an important role in asthma and the current thinking is that undertreatment of airways inflammation may lead to long-term structural changes such as airways remodelling and irreversible airflow obstruction [6]. While studies have documented pulmonary function abnormalities and bronchial hyperresponsiveness in previous childhood asthmatics [2,[7][8][9][10][11], to the best of the authors9 knowledge there are no reports of persistent airways inflammation in children who have outgrown asthma. This study examined direct measures of airways inflammation in children who had had wheezing episodes in the past.…”
mentioning
confidence: 99%